Principles of vaccine potency assays. (February 2018) - Verch, Thorsten; Trausch, Jeremiah J; Shank-Retzlaff, Mary
Compared with biologics, vaccine potency assays represent a special challenge due to their unique compositions, multivalency, long life cycles and global distribution. Historically, vaccines were released using in vivo potency assays requiring immunization of dozens of animals. Modern vaccines use a variety of newer analytical tools including biochemical, cell-based and immunochemical methods to measure potency. The choice of analytics largely depends on the mechanism of action and ability to ensure lot-to-lot consistency. Live vaccines often require cell-based assays to ensure infectivity, whereas recombinant vaccine potency can be reliably monitored with immunoassays. Several case studies are presented to demonstrate the relationship between mechanism of action and potency assay. A high-level decision tree is presented to assist with assay selection.